When Economic Growth Rhymes with Social Development: The Malaysia Experience - Naguib, Rabia (Journal of business ethics, 2009)
This article examines the means by which Malaysian governments have been relatively successful in pursuing both economic development and social equity. These advances have been remarkable, given Malaysia’s history of colonial servitude and racial and ethnic tensions. The authors’ examination of government economic and social policies notes the importance of strong political leadership that is committed to creating a national identity through consensus building. In pursuing these social objectives, successive governments have also played an active and transparent role in fostering economic growth and development. However, a number of problems remain as Malaysia continues to follow these social and economic policies.